A functional platform for remote use of electron microscopes using web conferencing systems. (26th May 2022) - Sugiura-Nakazato, Makoto; Takase, Hiroshi; Nakazato, Takeru
Abstract: We propose a useful system for remote sharing of transmission electron microscope (TEM) images by connecting three computers: a computer connected to a TEM, a computer distributing images and a computer receiving images. Then, we confirmed the performance of three web conferencing systems, Microsoft Teams, Zoom and Google Meet, to evaluate the usefulness of their remote use based on the clarity of images, smoothness of movement and time lag in images on each computer in the system. Display image of operation computer for TEM can be captured using the following two methods: a virtual camera of a video distribution software that provided a good reaction speed to transfer images and the screen sharing by conference system software that could share high-quality images.